POTENSI TUMBUHAN BERACUN SEBAGAI BAHAN BIOPESTISIDA DI CAGAR ALAM DOLOK SAUT - Fransiscus Sihombing; Irawati Azhar; Yunus Afifuddin (Program studi Kehutanan USU, 2016)
The very high use of chemical pesticides in the agricultural sector is more alarming nowadays. The negative impact of chemical pesticides are health problems in humans and damage to the environment, so it is necessary to find the alternative to overcome this problem. An alternative is by using biopesticides which utilizing poisonous plants that exist in nature. The research is conducted in the Cagar Alam Dolok Saut, Desa Pansur Natolu, Kecamatan Pangaribuan, Kabupaten Tapanuli Utara by using purposive sampling method and shaped transect sample plots, with a total of 98 plots. The purpose of this research is to identify the potential poisonous plants as a biopesticide in conservation area of Dolok Saut. There are 3 aspects of assessment that have been done; local knowledge aspect, diversity aspect and phytochemical aspect. Result shows that there are 9 types of poisonous plants that have been found: Apus Tutung (Clidemia hirta), Modang lalisiak (Ficus sinuata Thunb), Sitanggis (Belamcanda sp.) Dong-dong (Laportea stimulant Gaud) Antaladan (Xanthosoma sp.) Birah (Alocasia arifolia), Tahul-tahul (Nepenthes mirabilis), Bedi-bedi (Callicarpa dichotoma) and Langge (Homalomena javanica). All of samples are identified as having a potential to be used as biopestisida ingredients because they contain secondary metabolites alkoloid, saponins, tannins terpenes and flavonoids.